Factors Affecting Profitability: Empirical Study of Sharia Commercial Banks in Indonesia for the 2018-2022 Period - Robi Maulana M; Alan Rusdiana; Ulvy Fitrotul Azizah (Finance and Business Management Journal, 2023)
This study aims to find out how the effect of Intellectual Capital, Islamicity Performance Index and Corporate Social Responsibility on Profitability. This type of research is descriptive and verification research using a quantitative approach. The population in this study are Islamic Commercial Banks in Indonesia for the 2018-2022 period. The sampling technique uses purposive sampling, the samples used in this study amounted to 9 bank with a 5 years period of observation to 45sample data. the data used in this research is secondary data. The data analysis method in this study is descriptive, classical assumption test, multiple linear, coefficient of determination, model feasibility test and hypothesis testing with SPSS version 25 software tools. The results of this study indicate that intellectual capital affects profitability, meaning that the higher the intellectual capital, the lower the profitability. The Islamicity Performance Index affects Profitability, meaning that the higher the Islamicity Performance Index, the higher the profitability. And Corporate Social Responsibility has no effect on Profitability. Intellectual Capital, Islamicity Performance Index, and Corporate Social Responsibility have an effect on Profitability.